Exterior beam-column joint seismic behavior study using different joint core details with mechanical anchorage under reversal loading - Rajagopal, S.; Prabavathy, S. (Journal of Structural Engineering, 2024)
Generally the reinforced concrete structures in the high seismic prone zone, exterior beam - column joints are detailed with confinement and conventional 90° standard bent hooks for longitudinal beam reinforcement anchorages. This results in congestion of reinforcement in joint core. Also, the placement of reinforcement and concrete pouring during construction is difficult at site. An attempt has been made to study and evaluate the performance of beam-column joints with joint detailing as per ACI-352, ACI-318 and IS-456 along with confinement as per IS-13920 and without confinement. Apart from reducing congestion of reinforcement in joint core, significant improvement in seismic performance, strength, ductility, stiffness were observed while using mechanical anchorage (Headed bar) in combination with X-Cross bar plus U-bar joint reinforcement for higher seismic prone area. To assess the performances of these types of anchorages and joint details, six numbers of specimens were assembled into two groups, each having three specimens was tested under reversal loading. These experimental test results were evaluated and presented in this paper.